Mapping Adolescents Vulnerable to Early Marriage Using K-Means Clustering: Strategies for Nutrition Prevention - Putri, Dessya; Jannah, Miftahul; Puspita, Surya Dewi; Yuanta, Yohan (P3M Politeknik Negeri Jember, 2025)
Early marriage remains a critical public health concern with significant implications for adolescent reproductive health, nutrition, and socio-economic well-being. Adolescents who marry before reaching maturity face higher risks of malnutrition, anemia, and obstetric complications, while their children are more likely to experience low birth weight, stunting, and delayed development. Beyond health effects, early marriage limits educational attainment and employment opportunities, reinforcing intergenerational cycles of poverty. In Jember Regency, early marriage contributes to elevated Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), emphasizing the need for evidence-based prevention efforts. This study aimed to classify adolescents’ vulnerability to early marriage using the K-Means Clustering algorithm. A total of 30 adolescents aged 15–18 years from Karangpring Village, Sukorambi District, participated. Most respondents were 16 years old (53%), female (87%), and of Javanese ethnicity (90%). Data collected included demographics, as well as knowledge, attitudes, behaviors, and intentions related to early marriage. K-Means analysis generated three clusters: high-risk (30%), defined by limited knowledge, permissive attitudes, supportive behaviors, and strong intentions to marry early; moderate-risk (47%), showing average knowledge, mixed attitudes and behaviors, and situational intentions; and low-risk (23%), marked by better knowledge, rejecting attitudes toward early marriage, education-supportive behaviors, and minimal intentions. These findings show that cluster analysis offers a systematic approach to identifying adolescent vulnerability profiles. Such evidence is essential for guiding targeted, context-specific interventions to reduce early marriage and mitigate its health and social consequences.